THE RELATION BETWEEN NUMERICAL ABILITY, LEARNING INDEPENDENCE, LEARNING ENVIRONMENT AT HOME AND MATHEMATICS LEARNING OUTCOMES - Catur Sari Astutik; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2019)
Learning outcomes are presumably influenced by several factors, including numerical ability, learning independence, and learning environment at home. This study aims to determine whether there is a positive and significant relation between numerical ability, learning independence, learning environment at home. Mathematics learning outcomes of grade VIII students of Junior High School (SMP) Muhammadiyah 3 Yogyakarta, the Academic Year of 2017/2018. This study's population was grade VIII students of SMP Muhammadiyah 3 Yogyakarta in 2017/2018. A random sampling technique was applied to take this research sample, which is grade VIII C students. The data on numerical ability and mathematics learning outcomes were obtained through tests. Simultaneously, the data of the learning independence and learning environment at home were obtained through questionnaires. The research instruments were tested using a validity test, differential test, and reliability test. Analysis prerequisite tests include normality, linearity, and independence test. Simple regression and multiple linear regression analyses were used to analyze the data. The results show a positive and significant relation between numerical ability, learning independence, learning environment at home. Mathematics learning outcomes of grade VIII students of SMP Muhammadiyah 3 Yogyakarta in the Odd Semester of the Academic Year of 2017/2018. The F test results show . R = 0.495 and R2 = 0,245 with , with RC = 0.806%, RC =49.232% and RC = 49.962%. EC = 0.197%, EC = 12.064% and EC = 12.243%.